Performance evaluation of duty cycle balancing in power electronics enhanced battery packs compared to conventional energy redistribution balancing - Chatzinikolaou, E; Rogers, D (IEEE, 2018)
This paper presents a method for evaluating the performance of duty cycle balancing schemes and conventional energy redistribution active balancing schemes using a common linear programming framework. The framework is used to calculate the maximum usable capacity of a battery pack composed of cells of varying capacity coupled to a balancing circuit of a specified type and size. In the duty cycle balancing case the effect of cell redundancy for packs with DC and AC outputs is explored. In the energy redistribution case, balancing performance of different circuit topologies and circuit ratings is evaluated. An experimental validation of the numerical prediction for the duty cycle balancing method is conducted for a pack of twelve cells, where the duty cycle of each cell is controlled using a full-bridge circuit. In all cases the numerical and experimental results show an agreement in usable capacity to within 1%. The experimental results indicate that for a duty-cycle balanced pack constructed from cells with an extreme capacity range (where variation between cells is as large as the average cell capacity), the inclusion of two redundant cells in a 12 cell pack enables the extraction of 95% more capacity than in the case of no redundancy.